The use of nutrigenomics and nutritional biomarkers with standard care of long-term recurrent metastatic rectal cancer: a case report - Brinkman, Maree T.; Crofts, Sam; Green, Hayden (Frontiers in Oncology, 2024)
IntroductionDistant metastases following standard treatment for locally advanced rectal cancer (LARC) are typically associated with poor disease-free survival. We report on a 52-year-old Australian male of Dutch ancestry with no family history of colorectal cancer or significant medical history who experienced bleeding per rectum for several months prior to a colonoscopy in July 2010. He was subsequently diagnosed with Stage IIb LARC.Case presentationDespite treatment with curative intent, a distant recurrence to his left lung was detected in May 2012, upstaging him to Stage IV rectal cancer. He had repeated distant metastatic recurrences over the next 8 years, and treatment included multiple surgeries, chemotherapies, radiation treatments, a “watch and wait” period of 20 months, and personalised dietary management. Genetic and nutrigenomic testing identified that the case had KRAS and MTHFR mutations. As part of his dietary management, the case also had his levels of folate, vitamin B12, and vitamin D regularly monitored because of his genetic predisposition and history of deficiency for these key nutrients. Apart from changes in his CEA levels, sudden increases in the patient’s folate levels, inconsistent with dietary exposures preceded detection of each new distant recurrence, with significant decreases in the levels at the next follow-up measurement.ConclusionA multimodal approach to this patient’s management appeared to contribute to his long-term survival of nearly 10 years from the initial diagnosis. Multidisciplinary management, including the use of additional biomarkers, may enhance survival rates in other similar cases with advanced disease resistant to differing therapies, and with potentially poor prognosis.